1997
DOI: 10.1046/j.1365-2672.1997.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medium composition on the growth and antigen expression of Helicobacter pylori

Abstract: An evaluation of the ability of various solid and liquid media to support both growth and antigen expression, particularly lipopolysaccharide (LPS) expression, by Helicobacterpylori culture collection strains and clinical isolates was performed. Liquid‐based basal media (brain heart infusion, Brucella broth, Mueller–Hinton broth and tryptone soya broth) supported the growth of strains, whereas solid basal media of the same formulation did not support growth. Optimal growth of all strains was obtained on solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 41 publications
(11 reference statements)
7
88
0
2
Order By: Relevance
“…Although blood is the major iron source for some micro-organisms and enhances their growth, bile-tolerant Helicobacter spp., with the exception of H. hepaticus, were capable of growth on blood-free media. This indicates that blood is not essential for their growth, although it did enhance the growth of all these helicobacters, similar to previous observations with H. pylori (Walsh & Moran, 1997). Our data also indicated that hydrogen is an essential growth factor for bile-tolerant helicobacters, but the mechanism by which these organisms utilize hydrogen is poorly understood.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although blood is the major iron source for some micro-organisms and enhances their growth, bile-tolerant Helicobacter spp., with the exception of H. hepaticus, were capable of growth on blood-free media. This indicates that blood is not essential for their growth, although it did enhance the growth of all these helicobacters, similar to previous observations with H. pylori (Walsh & Moran, 1997). Our data also indicated that hydrogen is an essential growth factor for bile-tolerant helicobacters, but the mechanism by which these organisms utilize hydrogen is poorly understood.…”
Section: Discussionsupporting
confidence: 77%
“…remain difficult to culture from clinical samples. Various solid and broth culture media have been designed to optimize growth for the production of various antigens (Shahamat et al, 1991 ;Marchini et al, 1995 ;Walsh & Moran, 1997), to facilitate metabolic and enzyme studies, and to prevent accumulation of toxic metabolites that inhibit growth in the stationary phase (Hazell et al, 1989). However, culture media for Helicobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, individual colonies produced a stable LPS structure over subsequent subcultures. The culture media used here contained 10% (v/v) rather than the 7% (v/v) defibrinated horse blood used by Walsh and Moran (1997) and this small increase in blood content may influence LPS expression in these fastidious organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cultivation of H. pylori isolates on solid media may result in loss of the antigenic O side-chain (8). Also, specific mutants of the original organisms can be made by adjusting the culture condition (9,10).…”
Section: Introductionmentioning
confidence: 99%